Impact of Heat Treatment on Dimensional Stability of Salix tetrasperma Roxb. Wood - Shabir, Sufiya; Dutt, Bhupender; Kumar, Rajneesh; Sharma, Dineesh; Bhat, Gulam Mohidiun; Gupta, Heena (International Journal of Bio-resource and Stress Management, 2024)
The present investigation was carried out during the years October, 2021–September, 2022 in the Laboratory of the Department of Forest Products, Dr. Y S Parmar University of Horticulture and Forestry Nauni, Solan. Thermal modification was performed on the samples of Salix tetrasperma at various temperatures 60, 80, 100, 120, 140, 160 and 200°C for 2, 4 and 6h under stability oven, to asses its impact on wood dimensional stability. The data pertaining on maximum moisture content, swelling coefficient and shrinkage coefficient shows significant variation. The maximum moisture content at different temperature treatment, was recorded to be maximum (192.03%) in control and minimum (140.09%) at 200°C, whereas for durations the maximum moisture content (164.77%) was observed at 2 h while minimum (161.77%) at 6 h. Among interactions, the maximum value (192.03%) was observed in control and minimum (139.42%) was found at 200°C (6 h). In volumetric swelling and shrinkage coefficient, maximum values (8.03%) and (7.42%) among temperatures were found in control and minimum values (3.85%) and (3.42%) were observed at 200°C (6 h). Among durations, the highest values (5.94%) and (5.73%) were found at 2 h and the lowest values (5.60%) and (5.50%) were observed at 6h. The interactions in volumetric swelling coefficient showed significant results and the highest value (8.03%) was noticed in control and the lowest value (3.74%) at 200°C (6 h), However, interactions in volumetric shrinkage coefficient were found to be non-significant. This indicated that after thermal treatment, wood becomes less hygroscopic and exhibits less wear and tear, even in a harsh environment.